EKOLOGI SPIRITUAL SERTA NILAI EKONOMI DI PONDOK PESANTREN TAHFIDZUL QUR’AN IMAM SYAFI’I BREBES - Hakim, Abdul (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Spiritual ecology is a holistic approach that integrates religious values with environmental awareness, which, in the context of Islamic boarding schools (pondok pesantren), has developed into practices that are not only religiously meaningful but also economically beneficial. This study aims to analyze how pesantren implement the principles of spiritual ecology while simultaneously developing economic values in environmental management. Using a descriptive qualitative method, the research was conducted through case studies at several pesantren that run productive environmental programs such as organic farming, integrated livestock systems, and waste processing into marketable products. The results indicate that Islamic values such as the responsibility as stewards of the Earth (khalifah), simplicity, and sustainability serve as the foundation for all environmental activities. At the same time, pesantren are able to foster economic self-sufficiency through the wise and productive utilization of natural resources. These findings suggest that the practice of spiritual ecology in pesantren not only enhances ecological awareness but also creates economic impacts that support institutional independence. This study recommends strengthening the integration of environmental education, spirituality, and sustainable entrepreneurship within the pesantren environment